LECTURER’S STRATEGIES IN ENGLISH SPEAKING CLASS - Herlina Daddi; Muhammad Zia ul Haq (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2014)
This research aimed to reveal (1) what strategies were applied by lecturers in English speaking class, (2) how those strategies were applied and (3) to know the students’ perceptions toward the use of those strategies.This research employed qualitative grounded theory design. The subjects of the research were two non-native English lecturers who taught at the same private university in Makassar. The instruments of research were; observation, interview, and documents examination. The technique of data analysis adopted three series of codification of grounded theory approach; open coding, axial coding, and selective coding.The result of this research revealed five categories of strategies that applied by the two subjects. They were; (1) strategy of checking attendance, (2) strategy of seating arrangement, (3) strategy of teaching-learning activity, (4) strategy of correction and (5) strategy of assessment. Strategy of checking attendance, they were: numbering and one-off calling name; strategy of seating arrangement, they were: one-big circle, two circle, U-model, and island model; strategy of teaching-learning activity, they were: audio-based presentation, topic-based presentation, peer share idea, role play, discussion, and simulation; strategy of correction, they were: teacher correction and peer correction; and strategy of assessment, that was: performance-based assessment. In accordance with those strategies, the students raised perception that those strategies encouraged them to be good at speaking in terms of improving their confidence to share idea, vocabulary, pronunciation, and grammar.Keywords: Lecturer’s Strategy, Teaching Speaking, Perception